2019
DOI: 10.3390/ijms20246178
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Extracellular Vesicles Containing Xenobiotic Metabolizing CYP Enzymes and Their Potential Roles in Extrahepatic Cells Via Cell–Cell Interactions

Abstract: The cytochrome P450 (CYP) family of enzymes is known to metabolize the majority of xenobiotics. Hepatocytes, powerhouses of CYP enzymes, are where most drugs are metabolized into non-toxic metabolites. Additional tissues/cells such as gut, kidneys, lungs, blood, and brain cells express selective CYP enzymes. Extrahepatic CYP enzymes, especially in kidneys, also metabolize drugs into excretable forms. However, extrahepatic cells express a much lower level of CYPs than hepatocytes. It is possible that the liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 120 publications
(177 reference statements)
1
31
0
Order By: Relevance
“…Epoxyeicosatrienoic acids (EETs), the cytochrome P450 (CYP) epoxygenases-derived metabolites of arachidonic acid, exert a critical role in vascular functions by regulating the membrane hyperpolarization of smooth muscle cells (22). A recent study revealed that EETs induced the expression of VEGF and promoted angiogenesis in endothelial cells (ECs) (23).…”
Section: Introductionmentioning
confidence: 99%
“…Epoxyeicosatrienoic acids (EETs), the cytochrome P450 (CYP) epoxygenases-derived metabolites of arachidonic acid, exert a critical role in vascular functions by regulating the membrane hyperpolarization of smooth muscle cells (22). A recent study revealed that EETs induced the expression of VEGF and promoted angiogenesis in endothelial cells (ECs) (23).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they likely play an important mechanistic role in communication between the liver and the immune system. They have been studied both in patients and in animal models of liver injury (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Belonging to the group of extracellular vehicles comprising also microvesicles and apoptotic bodies ( 40), exosomes represent vesicles, which are commonly derived from cell membranes of various organs including the liver (39).…”
Section: Blood Exosomesmentioning
confidence: 99%
“…They can be found primarily in the liver but also in various other organs, such as the gut, brain, kidneys, and lungs [100,101]. Notably, CYPs also circulate in the bloodstream in CYP-containing extracellular vesicles [102].…”
Section: Metabolic Functionality and Response Assessmentmentioning
confidence: 99%